Engineering legume for drought stress tolerance: Constraints, accomplishments, and future prospects - Jalal, Arshad [UNESP]; Rauf, Kamran [UNESP]; Iqbal, Babar; Khalil, Rabia; Mustafa, Hayat; Murad, Muhammad; Khalil, Farhan; Khan, Sulaiman; Oliveira, Carlos Eduardo da Silva [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (Elsevier, 2023)
Drought is one the most devastating issue to agriculture productivity and food security in the current climate extremes. The current review focused on research-based engineering of cowpea with genetic potential to improve growth and reduce yield losses under drought. In recent years, genetic analysis has carried out to identify quantitative trait loci (QTL) markers that affect drought-related attributes. Some other studies highlighted the relationship between drought response and yield components, morphological and physiological attributes. To our knowledge, few studies are conducted on the identification of QTLs in cowpea for drought tolerance. The complexity of drought stress response repeated evaluations of individual attribute in marker-assisted selection made it more difficult. Although, extensive studies have conducted on cowpea drought-tolerance screening while only a few have been successfully implemented for the selection of parental genotypes. Drought tolerance in seedlings was closely related to drought tolerance in reproductive stage. The genotypes of candidate genes were selected on the basis of differential screening to identify cDNAs that make up genes for different drought tolerance pathways in cowpea. The genetics of drought tolerance and identification of DNA markers associated with QTLs open a clear path to identify chromosomal or candidate genes involved in drought resistance. It will help the cowpea breeders to use marker-assisted selection to develop improved genotypes of integrated characters of drought tolerance and other desired phenotypes for the welfare of farmers.
Keywords: Drought tolerance; Genes; Genomic regions; Legumes; Phenotyping; QTLs; Root architectures